Rekonstruksi Paradigma Integratif Ekonomi Syari’ah Kontemporer dalam Perspektif Maqashid al-Syari’ah - Anggita Maghfirotul Ismanudin; Muhammad Zainulloh; Muhammad Amin Fathih (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2026)
The development of contemporary Islamic economics demonstrates significant growth both institutionally and regulatorily. However, amid this expansion, criticism has emerged that Islamic economics tends to be trapped within a formal-legalistic approach that emphasizes legal compliance, while the dimensions of ethics and social justice have not been adequately integrated. This article aims to reconstruct the paradigm of contemporary Islamic economics through a conceptual analysis that integrates normative texts, Islamic ethics, and social realities within the framework of maqāṣid al-sharī‘ah. This study employs a qualitative approach, specifically library research, combined with a conceptual approach through the analysis of contemporary Islamic economics and Islamic studies literature. The findings indicate that the dominance of the formal-legal paradigm has led to the marginalization of Islamic ethics and weakened the transformative capacity of Islamic economics. Furthermore, there exists a tension between the idealism of Islamic normative texts, which are oriented toward justice, and the reality of Islamic economic practices, which tend to be less inclusive. This article proposes a reconstruction of an integrative Islamic economics paradigm that positions Islamic economics as both an ethical system and a social practice oriented toward public welfare (maṣlaḥah). Within this integrative paradigm, Islamic economics is understood not merely as a system of legal compliance, but as an instrument of social transformation that is responsive to contemporary challenges.